2018
DOI: 10.3390/en11082063
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of Long-Term Forecasting Model on Final Energy Consumption in Thailand’s Petroleum Industries Sector: Enriching the LT-ARIMAXS Model under a Sustainability Policy

Abstract: Presently, Thailand runs various sustainable development-based policies to boost the growth in economy, society, and environment. In this study, the economic and social growth was found to continuously increase and negatively deteriorate the environment at the same time due to a more massive final energy consumption in the petroleum industries sector than any other sectors. Therefore, it is necessary to establish national planning and it requires an effective forecasting model to support Thailand’s policy-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…In addition, this should agree with the regression equation, in which there is no problem of multicollinearity, no problem of heteroscedasticity, no problem on autocorrelation, and no problem of non-normality. The formative model differs from the reflective model as follows [4,62]:…”
Section: Second Order Autoregressive-semmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this should agree with the regression equation, in which there is no problem of multicollinearity, no problem of heteroscedasticity, no problem on autocorrelation, and no problem of non-normality. The formative model differs from the reflective model as follows [4,62]:…”
Section: Second Order Autoregressive-semmentioning
confidence: 99%
“…These include measures in the industries of transportation, textiles, iron and steel, and other industrial products that are exclusively outside of the agricultural sector. In addition, with respect to the long run, the government has implemented a number of different strategies, such as promoting exports and diversifying products for export, encouraging foreign direct investment, developing the tourism industry, improving labor skills for heavy industry, expanding local markets for foreign investors, adjusting the tax basis, and developing large industries of the government among many others [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the authors conducted other studies to support the forecasting models with different indicators. Those studies are titled "The efficiency of long-term forecasting model on final energy consumption in Thailand's petroleum industries sector: enriching the LT-ARIMAXS Model under a sustainability policy" [91] and "A relational analysis model of the causal factors influencing CO 2 in Thailand's industrial sector under a sustainability policy adapting the VARIMAX-ECM Model" [92]. The mentioned studies used a stationary process, while adapting the concept of a co-integration and error correction mechanism in order to analyze Energies 2019, 12, 3092 8 of 21 the real impact of the indicators on the dependent variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be observed that the number of parameters in the VAR(1) model is less than the SEM-VARIMAX(1) model's. Even though all the parameters can be estimated in the VAR(1) model, we still cannot use the relationship between the parameters of both models to find the parameter estimator in the SEM-VARIMAX(1) model [91,92].…”
mentioning
confidence: 99%
“…Sutthichaimethee and Kubaha [30] applied LT-ARIMAXS (the Long Term-Autoregressive Integrated Moving Average with Exogeneous variables and Error Correction Mechanism model) to conduct energy consumption long-term forecasting for the petroleum industry in Thailand.…”
Section: Energy Forecastingmentioning
confidence: 99%